Anthropomorphism in Human–Animal Interactions: A Pragmatist View - Servais, Véronique (Frontiers in Psychology, 2018)
This paper explores anthropomorphism in human-animal interactions from the theoretical perspectives of pragmatism and anthropology of communication. Its aim is to challenge the conception of anthropomorphism as the attribution/inference of human properties to a nonhuman animal, i.e. as a special case of the theory of mind, and to articulate and make plausible an alternative conception of anthropomorphism as a situated direct perception of human properties by someone who is engaged in a given situation, and let themselves be affected by the animal. The paper offers an original perspective for in depth ethnographic and empirical studies of anthropomorphism-in-situation. Such studies could bring new insights in the study of how ordinary people make sense of animal’s behaviors in real-life situations.